Wilhelm Wundt's Theory of Interpretation - Jochen Fahrenberg (Forum: Qualitative Social Research, 2008)
Wilhelm WUNDT was a pioneer in experimental and physiological psychology. However, his theory of interpretation (hermeneutics) remains virtually neglected. According to WUNDT psychology belongs to the domain of the humanities (Geisteswissenschaften), and, throughout his books and research, he advocated two basic methodologies: experimentation (as the means of controlled self-observation) and interpretative analysis of mental processes and products. He was an experimental psychologist and a profound expert in traditional hermeneutics. Today, he still may be acknowledged as the author of the monumental Völkerpsychologie, but not his advances in epistemology and methodology. His subsequent work, the Logik (1908/1921), contains about 120 pages on hermeneutics. In the present article a number of issues are addressed. Noteworthy was WUNDT's general intention to account for the logical constituents and the psychological process of understanding, and his reflections on quality control. In general, WUNDT demanded methodological pluralism and a complementary approach to the study of consciousness and neurophysiological processes. In the present paper WUNDT's approach is related to the continuing controversy on basic issues in methodology; e.g. experimental and statistical methods vs. qualitative (hermeneutic) methods. Varied explanations are given for the one-sided or distorted reception of WUNDT's methodology. Presently, in Germany the basic program of study in psychology lacks thorough teaching and training in qualitative (hermeneutic) methods. Appropriate courses are not included in the curricula, in contrast to the training in experimental design, observation methods, and statistics. URN: urn:nbn:de:0114-fqs0803291